Quantification of seasonal and diurnal dynamics of subglacial channels using seismic observations on an Alpine glacier - Nanni, Ugo; Gimbert, Florent; Vincent, Christian; Gräff, Dominik; Walter, Fabian; Piard, Luc; Moreau, Luc (The Cryosphere, 2020)
International audience Water flowing below glaciers exerts a major control on glacier basal sliding. However, our knowledge of the physics of subglacial hydrology and its link with sliding is limited because of lacking observations. Here we use a 2-year-long dataset made of on-ice-measured seismic and in situ-measured glacier basal sliding speed on Glacier d'Argentière (French Alps) to investigate the physics of subglacial channels and its potential link with glacier basal sliding. Using dedicated theory and concomitant measurements of water discharge, we quantify temporal changes in channels' hydraulic radius and hydraulic pressure gradient. At seasonal timescales we find that hydraulic radius and hydraulic pressure gradient respectively exhibit a 2- and 6-fold increase from spring to summer, followed by comparable decrease towards autumn. At low discharge during the early and late melt season channels respond to changes in discharge mainly through changes in hydraulic radius, a regime that is consistent with predictions of channels' behaviour at equilibrium. In contrast, at high discharge and high short-term water-supply variability (summertime), channels undergo strong changes in hydraulic pressure gradient, a behaviour that is consistent with channels behaving out of equilibrium. This out-of-equilibrium regime is further supported by observations at the diurnal scale, which prove that channels pressurize in the morning and depressurize in the afternoon. During summer we also observe high and sustained basal sliding speed, which supports that the widespread inefficient drainage system (cavities) is likely pressurized concomitantly with the channel system. We propose that pressurized channels help sustain high pressure in cavities (and therefore high glacier sliding speed) through an efficient hydraulic connection between the two systems. The present findings provide an essential basis for testing the physics represented in subglacial hydrology and glacier sliding models.